"Internet+Nursing Service" Mobile Apps in China App Stores: Functionality and Quality Assessment Study - Shuo Yuan; Min Liu; Yuqi Peng; Jinrui Hu; Bingyan Li; Xia Ding; Lunfang Xie (JMIR Publications, 2024)
Abstract BackgroundAs the Chinese society ages and the concern for health and quality of life grows, the demand for care services in China is increasing. The widespread use of internet technology has greatly improved the convenience and efficiency of web-based services. As a result, the Chinese government has been implementing "Internet+Nursing Services" since 2019, with mobile apps being the primary tools for users to access these services. The quality of these apps is closely related to user experience and the smooth use of services. ObjectiveThis study aims to evaluate the functionality, services, and quality of "Internet+Nursing Service" apps; identify weaknesses; and provide suggestions for improving service programs and the research, development, improvement, and maintenance of similar apps. MethodsIn December 2022, two researchers searched for "Internet+Nursing Service" apps by applying the search criteria on the Kuchuan mobile app monitoring platform. After identifying the apps to be included based on ranking criteria, they collected information such as the app developer, app size, version number, number of downloads, user ratings, and number and names of services. Afterward, 5 trained researchers independently evaluated the quality of the apps by using the Chinese version of the user version of the Mobile App Rating Scale (uMARS-C). The total uMARS-C score was based on the average of the five evaluators' ratings. ResultsA total of 17 "Internet+Nursing Service" apps were included. Among these, 12 (71%) had been downloaded more than 10,000 times, 11 (65%) had user ratings of 4 or higher, the median app size was 62.67 (range 22.71‐103; IQR 37.51-73.47) MB, 16 (94%) apps provided surgical wound dressing change services, 4 (24%) covered first-tier cities, and only 1 (6%) covered fourth-tier cities. The median total uMARS-C score was 3.88 (range 1.92-4.92; IQR 3.71-4.05), which did not correlate with app store user ratings (rP Conclusions"Internet+Nursing Service" apps need to broaden their service coverage, increase service variety, and further optimize their service structure. The overall quality of these apps is generally poor. App developers should collaborate with medical professionals and communicate with target users before launching their products to ensure accurate content, complete functionality, and good operation that meets user needs.